2022
DOI: 10.3389/fpubh.2022.912922
|View full text |Cite
|
Sign up to set email alerts
|

Food spending in the United States during the first year of the COVID-19 pandemic

Abstract: The COVID-19 pandemic brought about a significant increase in the unemployment rate and a decline in consumer income. At the same time, the public health responses to the pandemic, such as lockdowns and business closures, disrupted the food supply chain. These pandemic-driven changes could lead to a shift in food spending behaviors and potentially exacerbate the food insecurity situation. Leveraging the nationally representative dataset from the 2017–2020 consumer expenditure surveys, we employ a two-part mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
1
1
Order By: Relevance
“…Interestingly, a substantial number of our respondents had no prior experience with online grocery shopping and grocery pickup services. This differs from previous studies reporting an upward trend in these services [ 19 , 32 , 38 ]. Our study participants were mostly individuals ranging from ages 18–24 years.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a substantial number of our respondents had no prior experience with online grocery shopping and grocery pickup services. This differs from previous studies reporting an upward trend in these services [ 19 , 32 , 38 ]. Our study participants were mostly individuals ranging from ages 18–24 years.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of our study support previous research indicating a rise in online grocery shopping and grocery pickup services during the COVID-19 pandemic [ 36 , 37 ]. Our study also found that the pandemic has led to increased acceptance of grocery pickup among the participants in agreement with previous findings [ 17 , 38 ]. Interestingly, a substantial number of our respondents had no prior experience with online grocery shopping and grocery pickup services.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, in 2020, the average expenditure outside the household was three times lower than inside the household. In our study, the survey year (i.e., 2019 vs. 2020) was not an effect modifier, which is consistent with an analysis of food expenditure in the first year of the pandemic, in which no visible effect of the total food expenditure available to the household was noted 43 . This latter analysis was performed using national surveys with a similar methodology as that used in the present work.…”
Section: Discussionsupporting
confidence: 91%
“…The continued increase of at-home cooking may be a long-term effect of lockdowns and restricted access to fast food and restaurants during this period. During the acute phase of the pandemic, consumption of fast foods was reduced [ 60 , 61 ], but students in the present study reported that consumption of fast foods was more or about the same as pre-pandemic, which may be a result of the increased need for socialization after restrictions were removed. Consistent with other studies of changes in consumption patterns in university students, we found a self-reported increase in alcohol consumption [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 78%